Osteoclast development from peripheral blood monocytes is reduced in patients with radiographic axial spondyloarthritis on biological therapy - Cecilia Engdahl; Malin C. Erlandsson; Magnus Hallström; Anna Deminger; Helena Forsblad-d’Elia (Arthritis Research & Therapy)
Abstract Background Radiographic axial spondyloarthritis (r-axSpA) is a chronic inflammatory disease that primarily affects the axial skeleton and entheses, leading to pathological spinal bone formation and systemic bone loss. Treatments with tumor necrosis factor inhibitors (TNFi) and interleukin-17 inhibitors (IL-17i) have shown efficacy in reducing inflammation and potentially impacting bone remodeling in r-axSpA. Osteoclasts, crucial for bone resorption, are derived from the monocytic cell lineage and regulated by proinflammatory cytokines. This study aimed to evaluate the osteoclast development capacity from peripheral blood monocytes in patients with r-axSpA with different treatment strategies and compare it to controls. Methods This study included 28 patients with long-standing r-axSpA receiving various treatments, including disease-modifying anti-rheumatic drugs (DMARDs) and NSAIDs, as well as 16 blood-donor controls. Disease activity was assessed using the Ankylosing Spondylitis Disease Activity Score (ASDAS). CD14 + monocytes were isolated from blood samples and differentiated into osteoclasts in vitro by stimulation with three different conditions: (I) macrophage colony-stimulating factor (M-CSF), (II) M-CSF and receptor activator of nuclear factor-κβ (RANKL), and (III) M-CSF, RANKL, and tumor necrosis factor-alpha (TNF). Osteoclast and osteoclast precursor formation were assessed using tartrate-resistant acid phosphatase (TRAP) staining, and TRAP5b concentration in supernatants was measured by ELISA. Results The frequency of CD14 + monocytes was similar in patients with r-axSpA and controls, but the capacity to develop osteoclasts and osteoclast precursors was significantly decreased in the r-axSpA patients. Stratification of the patients based on treatment with or without biological DMARDs (bDMARDs) revealed no significant differences in ASDAS or frequency of CD14 + monocytes. Notably, only r-axSpA patients receiving bDMARDs exhibited a reduced ability to develop osteoclasts and osteoclast precursors compared to those not on bDMARDs and controls. Lower Trap5b concentrations in supernatants corroborated these findings. Conclusions Our study demonstrates that patients with r-axSpA exhibit a reduced capacity for osteoclast formation from CD14 + monocytes isolated from peripheral blood. The process was modulated by treatment with bDMARDs, which might explain the previously shown sparing effect of bDMARDs on bone mineral density in r-axSpA.